An Initial Study Of The Air Pollution Through Rainwater In An Industrial Area Of Bekasi - Izzati, Titia (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2016)
This study aims to determine the level of acidity in the rainwater in the industrial area of East Jakarta. The research was done by using a multimeter (Waterproof Tester). With these tools, it can be seen pH and temperature in the rainwater. The results shown that the rainwater in the area of Bekasi tends to be normal because it is still in the average and standard. Although these areas are industrial areas, airports, and many transportation passes, the industrial area still have green places.